Optimal bidding strategy of electricity retailers using robust optimisation approach considering time‐of‐use rate demand response programs under market price uncertainties - Nojavan, Sayyad; Mohammadi‐Ivatloo, Behnam; Zare, Kazem (IET generation, transmission & distribution, 2015)
In restructured electricity markets, the electricity retailers try to obtain the consumers' electricity demand at the minimum cost of different resources such as self‐generating facilities, bilateral contracts and pool market purchases. Hence, more attention should be paid to the demand response programs (DRPs) which aim to electricity procurement cost reduction. Owing to the uncertain nature of pool prices and the price fluctuation in the pool markets, the uncertainty modelling is inevitable for retailers. In this study, a robust optimisation approach is proposed for decision making of electricity retailers. Meanwhile, considering the effect of DRP on total procurement cost, an optimal bidding strategy is proposed of electricity retailers with the time‐based model of DRP in the electricity market. For this purpose, a collection of robust mixed‐integer linear programming (RMILP) problem should be solved in the proposed method. Rather than using the forecasted prices as inputs, the upper and lower limits of pool prices are considered for the uncertainty modelling. The range of pool prices is sequentially partitioned into successive nested subintervals, which permits formulating the RMILP problems. The results of these problems give sufficient data to obtain an optimal bidding strategy for electricity retailers considering DRP. Detailed analysis is performed to delineate the proposed method.